Sex differences in clinical outcomes for obstructive hypertrophic cardiomyopathy in the USA: a retrospective observational study of administrative claims data. Issue 3 (9th March 2022) - Butzner, Michael; Leslie, Douglas; Cuffee, Yendelela; Hollenbeak, Christopher S; Sciamanna, Christopher; Abraham, Theodore P
Abstract : Objectives: To evaluate sex differences in demographic and clinical characteristics, treatments and outcomes for patients with diagnosed obstructive hypertrophic cardiomyopathy (oHCM) in the USA. Setting: Retrospective observational study of administrative claims data from MarketScan Commercial Claims and Encounters Database from IBM Watson Health. Participants: Of the 28 million covered employees and family members in MarketScan, 9306 patients with oHCM were included in this analysis. Main outcome measures: oHCM-related outcomes included heart failure, atrial fibrillation, ventricular tachycardia/ fibrillation, sudden cardiac death, septal myectomy, alcohol septal ablation (ASA) and heart transplant. Results: Among 9306 patients with oHCM, the majority were male (60.5%, p<0.001) and women were of comparable age to men (50±15 vs 49±15 years, p<0.001). Women were less likely to be prescribed beta blockers (42.7% vs 45.2%, p=0.017) and undergo an implantable cardioverter-defibrillator (1.7% vs 2.6%, p=0.005). Septal reduction therapy was performed slightly more frequently in women (ASA: 0.08% vs 0.05%, p=0.600; SM: 0.35% vs 0.18%, p=0.096), although not statistically significant. Women were less likely to have atrial fibrillation (6.7% vs 9.9%, p<0.001). Conclusion: Women were less likely to be prescribed beta blockers, ACE inhibitors, anticoagulants, undergo implantable cardioverter-defibrillator and have ventricular tachycardia/fibrillation. Men were more likely to have atrial fibrillation. Future research using large, clinical real-world data are warranted to understand the root cause of these potential treatment disparities in women with oHCM.